Effects of caffeine and ginseng supplementation on endurance performance in the heat - Wong Chee, Ping (2008)
Athletes in Malaysia need to perform in a hot and humid environment due to the climatic nature of the country. Alteration in endurance performance following acute and chronic supplementation of caffeine has been studied in different populations but concurrent research in the Malaysian context has not been attempted before. Equivocal findings of the ergogenic properties of Panax ginseng in enhancing physical performance were reported. However, data on the effect of acute supplementation of Panax ginseng on physical performance among Malaysian population is still lacking. Furthermore, combination of caffeine and Panax ginseng has never been investigated before on endurance running performance in the heat. In the present study, we examined the effect of acute supplementation of 5 mg caffeine per kg of body weight (C), 200 mg Panax ginseng (PG), combination of 5 mg caffeine per kg of body weight and 200 mg Panax ginseng (CPG) or placebo (PL) consumed one hour prior to the endurance performance. Supplements and placebo were given in the form of capsules in a randomised double blind cross-over trial. Nine heat acclimated recreational runners (aged: 25.4 + 6.9 years) as well as nonusers of caffeine (23.7.:!:. 12.6 mg per day) participated in this study. Subjects ran at 70% of their V02max on a motorised treadmill in a heat-controlled laboratory (31°C, 70% relative humidity). Subjects drank 3 ml of cool water per kg of body weight every 20 minutes during the trials to avoid the possibility of dehydration. Heart rate, mean skin temperature (chest, arm, thigh and calf), rectal temperature and RPE were recorded at an interval of 10 minutes. Oxygen consumption, fluid sensory scale and blood samples were collected at intervals of 20 minutes. Running time to exhaustion was significantly longer (p=0.04) in C trial compared to PI trial. However, the longer time to exhaustion in the CPG trial did not reach statistical significance (P=0.07). Exhaustion time in PG trial showed no significant difference (P=0.75) in comparison with PI trial. Heart rate, rectal temperatures, mean skin temperature, oxygen uptake, plasma insulin, glucose, lactate in the C, CPG and PG were not significantly different from the PI trial. Plasma free fatty acid in the C and CPG trial were significantly higher in comparison with PI trials. RPE were lowest in C trial and followed by CPG, PG and PL trials. Heart rate, rectal temperature, mean skin temperature, oxygen uptake, plasma insulin, glucose, lactate and fatty acid increased significantly during exercise from their respective resting values in all trials. Gastrointestinal discomfort was not reported during endurance performance in all trials. From the current study, it could be concluded that ingestion of 5 mg of caffeine per kg of body weight has an ergogenic effect on the nonusers of caffeine and heat-acclimatised recreational runners in a hot and humid environment.